Modern Indian political thought. - Varma, Vishwanath Prasad (Agra, 1961)
An attempt has been made in this book to present a systematic picture of modern Indian political ideas which are spread in a number of books, journals, newspaper files, pamphlets etc. This book is perhaps the first comprehensive attempt to analyze and expound the various phases, aspects and schools of modern Indian political thought. A few fine autobiographies like those of Mahatma Gandhi, Shraddhanand, Rajendra Prasad, Jawaharlal Nehru, Subhas Chandra Bose and M. R. Jaykar have also appeared. A few histories of modern Indian political and social movements like the Brahmo Samaj, the Arya Samaj, the Ramakrishna Movement, the Indian National Congress and Indian Communism have also been published. But this book is the first large-scale attempt to discuss systematically the explicit and implicit political ideas of the various political and social leaders and thinkers in modern India. Modern Indian political thought is a very vast subject. This book should be supplemented with my two other publications in this field: (1) The Political Philosophy of Mahatma Gandhi and Sarvodaya (Lakshmi Narain Agarwal, Agra) and (2) The Political Philosophy of Sri Aurobindo (Asia Publishing House, Bombay & New York). These three books will, it is hoped, provide a thorough, critical and comparative account of modern Indian political thought. Modern Indian political thought is a growing and developing subject and as other schools come into being and crystallize their conceptions, place will have to be allotted to them in the history of political thinking.
Keywords: Political Science